Spiritual Growth Aspects among Caregivers of Children with Cancer - Saari, Che Zarrina; Wahed, Norwahizatul; Syed Muhsin, Sharifah Basirah; Zainal Abidin, Mohd Syukri; Ahmad, Siti Sarah; S.M.H.S.A., Rahman; S., Musa; S.Z., Ab Rahman; Z.A., Sabki; Chik, Hasimah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Spirituality is one of the essential aspects of one’s life. It offers a broader perspective towards a meaningful life while undergoing trials such as caring for children with cancers. Cancer caregivers commonly experience physical, emotional, social, and spiritual challenges. Spiritual issues such as lost hope and associating negative meanings with cancer prognosis may reduce the caregiver’s quality of life. However, this caregiving burden can be a great source of post-traumatic growth. Therefore, the objective of this study is to explore spiritual change, a significant domain in post-traumatic growth among 24 caregivers of children with cancer at one of the teaching hospitals in Kuala Lumpur. Following in-depth interviews, the result of the thematic analysis demonstrated two themes; main religious and mindfulness practices, a significant caregiver’s spiritual development. The majority of caregivers reported increasing spiritual awareness levels, feeling closer to God, and focused on religious practices as caregivers coping mechanisms and patients’ complementary therapy. Hence, spiritual concerns among families of children with cancer need to be addressed during cancer treatment. This study suggests the development of an appropriate quick reference on spiritual aspects for caregivers which would be useful during the cancer trajectory and improve the whole family’s quality of life.